Defect-Induced Modulation of Electronic and Optical Properties in Monolayer CsPb2Br5: Implications for Fiber-Optic Sensing Applications - Meiqi An; Wenxuan Fan; Shengsheng Wei; Junqiang Wang (Photonics)
Two−dimensional halide perovskites have emerged as promising optoelectronic materials, yet the uncontrolled defect formation during synthesis remains a critical challenge for their practical applications. In this work, we systematically investigate the structural, electronic, and optical properties of monolayer CsPb2Br5 in two representative configurations: ds−CsPb2Br5 and ss−CsPb2Br5. By introducing four types of vacancy defects—VBr−c, VBr−b, VCs, and VPb, we analyze their structural distortions, formation energies, and their impact on band structure and optical response using first−principles calculations. Our results reveal that Br−related vacancies are energetically most favorable and induce shallow defect levels and absorption edge redshifts in the ds−CsPb2Br5 structure, while in the ss−CsPb2Br5 configuration, only VBr−b forms a defect state. VPb and VCs lead to significant sub−bandgap absorption enhancement and dielectric response due to band−edge reorganization, despite not introducing in−gap states. Notably, VBr−c exhibits distinct infrared absorption in the ss−CsPb2Br5 model without electronic trap formation. These findings underscore the critical influence of defect type and slab asymmetry on the optoelectronic behavior of CsPb2Br5, providing guidance for defect engineering in perovskite−based optoelectronic applications.